(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
The fall of the socialist political system and after the independence of Macedonia, was followed by a period where the past was reexamined. A big part of the cultural heritage and the artifacts which, during the previous system were favored, were mostly neglected in the new situation with an explanation that they had been a tool of the single-party system. The current pluralistic ideologies and political centers of power began to fight over the control and reinterpretation of the past, which had direct or indirect impacts on the definition or redefinition of the national identity.